Faktor loyalitas karyawan Generasi Z: Kepuasan kerja sebagai mediasi - Angela Adriyanti Yang; Yuli Indah Fajar Dini (Universitas Kristen Maranatha, 2023)
The presence of Gen Z in the workforce brings its own challenges for organizations. The unique characteristics and preferences of this generation compared to previous generations means that organizations need to consider factors that can influence satisfaction and loyalty of these employees in the workplace. Therefore, this study aims to examine how career development and work environment affects loyalty among Gen Z employees, mediated by job satisfaction. The population of the research consists of Gen Z employees, while the sample was from 389 Gen Z respondents who were working in Batam city, obtained through nonprobability with purposive sampling techniques. Questionnaire indicators were measured using Likert Scale and evaluated by Structural Equation Model (SEM) based on SmartPLS 3.0. Findings revealed that the increasing achievement of career goals and a more conducive work environment for Gen Z employees influenced their tendency to be more loyal to the organization, both directly and indirectly through the mediation of work satisfaction. However, the mediating variable in this study measured to only have a 38.3 percent influence on employee loyalty, indicating that the ability of job satisfaction is still constrained in explaining the dependent variable. Additionally, the object and sample employed only compromised Gen Z workers in Batam city, which means that it has not fully represented the entire Gen Z workforce.